2016
DOI: 10.1007/s13555-016-0152-3
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Kaposi’s Sarcoma: Epidemiology, Pathogenesis and Treatment

Abstract: Kaposi’s sarcoma is an angioproliferative neoplasm which has undergone considerable epidemiologic change since the original description by Moritz Kaposi in the late 1800s. This opportunistic neoplasm gained widespread notoriety within the US during the height of the AIDS epidemic, where it was frequently found co-occurring with opportunistic infections. With the advent of modern antiretroviral therapies, as well as an increasing number of individuals on immunosuppression for autoimmune disease or organ transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 32 publications
3
56
0
4
Order By: Relevance
“…Lesions may stay the same for months or become disseminated [1]. Su et al [6] reported that the duration of the lesions ranged between 3 months and 25 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lesions may stay the same for months or become disseminated [1]. Su et al [6] reported that the duration of the lesions ranged between 3 months and 25 years.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the treatment is to reduce symptoms, relieve lymphedema, reduce the number of lesions, and prevent progression. Local and systemic tumor-directed treatments can be used [1,4]. Given that KS does not affect life expectancy, effective local treatments should be considered as first line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…İyatrojenik Kaposi sarkomu özellikle organ transplantasyonu yapılan hastalarda immünsupresif tedavi alımına bağlı ortaya çıkmaktadır. Bununla birlikte başka nedenlerden dolayı uzun dönem kortikosteroid kullanımı, rituximab, infliximab ve abatacept içeren biyolojik ajanlarla tedavi alan hastalarda da sıklığı artmaktadır (8). Literatürde, 12 hasta ile yapılan bir çalışmada immünsupresif tedavi almaya devam eden hastaların %91,6'sında Kaposi sarkomuna bağlı cilt lezyonlarının arttığı, buna karşın immünsupresif tedavinin azaltılması durumunda ise %11,7 hastada greft reddi saptanmıştır.…”
Section: Discussionunclassified
“…Indeed, the Tat protein -with the help of its sequences of arginine and lysin -has properties which support not only the angiogenesis (by β-fibroblast growth factor and vascular endothelial growth factor A) but also the migration, proliferation, and expression of affected cells [7,8]. The elementary dermatological lesion in KS is an erythematous, angiomatous, and purplish macule which infiltrates gradually to become a papule, then a nodule, finally leading to the formation of broad plates resulting from the junction of budding cutaneous lesions; in addition, lymphedemas are seen more often [6,9].…”
mentioning
confidence: 99%